Optimal timing for repair of peripheral nerve injuries. Issue 5 (November 2017) - Wang, Eugene; Inaba, Kenji; Byerly, Saskya; Escamilla, Diandra; Cho, Jayun; Carey, Joseph; Stevanovic, Milan; Ghiassi, Alidad; Demetriades, Demetrios
Abstract : BACKGROUND: Data regarding outcomes after peripheral nerve injuries is limited, and the optimal management strategy for an acute injury is unclear. The aim of this study was to examine timing of repair and specific factors that impact motor-sensory outcomes after peripheral nerve injury. METHODS: This was a single-center, retrospective study. Patients with traumatic peripheral nerve injury from January 2010 to June 2015 were included. Patients who died, required amputation, suffered brachial plexus injury, or had missing motor-sensory examinations were excluded. Motor-sensory examinations were graded 0 to 5 by the Modified British Medical Research Council system. Operative repair of peripheral nerves was analyzed for patient characteristics, anatomic nerve injured, level of injury, associated injuries, days until repair, and repair method. RESULTS: Three hundred eleven patients met inclusion criteria. Two hundred fifty-eight (83%) patients underwent operative management, and 53 (17%) underwent nonoperative management. Those who required operative intervention had significantly more penetrating injuries 85.7% versus 64.2% ( p < 0.001), worse initial motor scores 1.19 versus 2.23 ( p = 0.004), and worse initial sensory examination scores 1.75 versus 2.28 ( p = 0.029). Predictors of improved operative motor outcomes on univariate analysis were Injury Severity Score less than 15 ( p = 0.013) and male sex ( p = 0.006). Upper arm level of injury was a predictor of poor outcome ( p = 0.041). Multivariate analysis confirmed male sex as a predictor of good motor outcome ( p = 0.014; Adjusted Odds Ratio, 3.88 [1.28–11.80]). Univariate analysis identified distal forearm level of injury ( p = 0.026) and autograft repair ( p = 0.048) as predictors of poor sensory outcome. Damage control surgery for unstable patients undergoing laparotomy ( p = 0.257) and days to nerve repair ( p = 0.834) did not influence motor-sensory outcome. Outcomes did not differ significantly in patients who underwent repair 24 hours or longer versus those who were repaired later. CONCLUSION: Outcomes were primarily influenced by patient characteristics and injury level rather than operative characteristics. Peripheral nerve injuries can be repaired after damage control surgery without detriment to outcomes. LEVEL OF EVIDENCE: Prognostic study, level III. Abstract : Supplemental digital content is available in the text.